2005
DOI: 10.1016/j.jacc.2005.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Plant Sterols in Serum and in Atherosclerotic Plaques of Patients Undergoing Carotid Endarterectomy

Abstract: The higher the absorption of cholesterol, the higher are the plant sterol contents in serum resulting also in their higher contents in atherosclerotic plaque. However, the role of dietary plant sterols in the development of atherosclerotic plaque is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 18 publications
4
60
1
Order By: Relevance
“…Accordingly, these studies cannot be used together as supporting evidence that CHD risk is associated with moderately elevated plasma PS concentrations. Other data (Rajaratnam et al, 2000;Sudhop et al, 2002;Miettinen et al, 2005) do reinforce an association between plasma PS and CHD risk for both campesterol and sitosterol. Nevertheless, the proportion of cholesterol to PS concentrations in serum and plaque tissue and the ratio PS/cholesterol remained the same, suggesting no preferential uptake of PS into plaque tissue and thus no accelerated accumulation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Accordingly, these studies cannot be used together as supporting evidence that CHD risk is associated with moderately elevated plasma PS concentrations. Other data (Rajaratnam et al, 2000;Sudhop et al, 2002;Miettinen et al, 2005) do reinforce an association between plasma PS and CHD risk for both campesterol and sitosterol. Nevertheless, the proportion of cholesterol to PS concentrations in serum and plaque tissue and the ratio PS/cholesterol remained the same, suggesting no preferential uptake of PS into plaque tissue and thus no accelerated accumulation.…”
Section: Discussionmentioning
confidence: 88%
“…Certain studies suggest that moderately elevated plasma PS concentrations are associated with a greater CHD risk (Glueck et al, 1991;Rajaratnam et al, 2000;Sudhop et al, 2002;Miettinen et al, 2005;Assmann et al, 2006). Glueck et al (1991) suggested a relationship between campesterol, but not sitosterol, concentrations and CHD risk in a study of 565 hypercholesterolemic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation from the Dallas Heart Study showed no relationship between plasma phytosterols and a surrogate marker for CHD, namely, coronary calcium scores measured by electron beam computed tomography ( 26 ). Miettinen et al ( 27 ) reported an association between raised plasma phytosterol levels and increased phytosterol content of surgically removed carotid plaques, while Weingärtner et al ( 28 ) showed that consumption of phytosterol-enriched margarine correlated with increased plasma concentrations and tissue deposi- An additional factor that infl uences plasma phytosterolto-cholesterol ratios is statin treatment ( 7,36 ), a reason why statin users were excluded from the analyses. Finally, the plasma sitosterol and campesterol ratios to cholesterol were in the same physiological range as reported in previous studies (9)(10)(11)(12)(13)(14)(15)30 ), strengthening the reliability of our data.…”
Section: Characteristics Of Chd Cases and Matched Controlsmentioning
confidence: 99%
“…Sitosterolaemia is associated with increased atherosclerosis [2]. The higher the absorption of cholesterol, the more plant sterol is found in the atherosclerotic plaque [3]. The intestinal cholesterol transporter, Niemann-Pick C1-like 1 (NPC1L1), regulates cholesterol absorption and NPC1L1 mRNA is increased in type 2 diabetic patients [4].…”
mentioning
confidence: 99%